Dynamic intermolecular interactions through hydrogen bonding of water promote heat conduction in hydrogels. Issue 11 (28th August 2020) - Zhou, Jiawei; Lin, Shaoting; Zeng, Hongxia; Liu, Ji; Li, Buxuan; Xu, Yanfei; Zhao, Xuanhe; Chen, Gang
Abstract : Dynamic intermolecular forces through hydrogen bonding between water and polymer chains are shown to enhance thermal transport in soft materials. Abstract : Heat-conducting polymers provide a new opportunity to tackle thermal management challenges in advanced technologies such as wearable electronics and soft robotics. One strategy to enhance heat conduction in amorphous polymers has been tuning their intermolecular interactions. These intermolecular forces are often static in nature as the participating molecules are anchored on the polymer chains. In this work, using hydrogel as a model system, we demonstrate how dynamic intermolecular forces, which break and re-form constantly, can also enhance thermal transport. Utilizing calorimetric and spectroscopic measurements, we show that this arises from the hydrogen bonds formed between water and nearby polymer chains, which enhances the inter-chain heat transfer efficiency. This mechanism may potentially allow the design of heat-conducting polymers with self-healing or adaptability functionalities.